Dielectric, ferroelectric and piezoelectric properties of sputtered PZT thin films on Si substrates: influence of film thickness and orientation - Haccart, T.; Cattan, E.; Remiens, D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Lead titanate zirconate Pb(Zr,Ti)O₃ (PZT) thin films were deposited on platinized silicon substrates by r.f. magnetron sputtering and crystallized with preferred (110) or (111) orientation by conventional annealing treatment. The film structure evolution was observed as a function of the film thickness. Whatever the film thickness in the range 0.07 - 3 mm, the preferred orientation of the film is maintained. The film microstructure and, in particular, grain sizes varied with the film thickness; more precisely, grain sizes increases, both for (111) and (110) films with the film thickness. The electrical properties such as dielectric, ferroelectric and piezoelectric ones were systematically evaluated functions of the film thickness and their orientation. The relative dielectric constant increases with the film thickness; a saturation value of 920 is attained for film thicknesses higher than 0.6 µm independently of the film orientation. The ferroelectric properties seems to be independent of the film orientation; the coercive field decrease with increasing the film thickness to attain a minimum value of 30 kV/cm for films thicker than 1 mm. The remanent polarization increases with the film thickness and reaches the maximum value of 20 mC/cm². An increase in the piezoelectric constant e₃₁ with increasing the film thickness was observed for two types of films. For films thicker than 0.6 mm, the e₃₁ coefficient remains constant: e₃₁eff.rem. = -4.5 C/m² (which corresponds to d₃₁eff.rem. = -38 pm/V). Identical behavior is observed for the d₃₃eff. coefficient but no saturation effect with the film thickness is observed. The ferroelectric domain walls motion and the interfacial effects could explain partly the observed behavior.